Inactivation of Zika virus by solvent/detergent treatment of human plasma and other plasma‐derived products and pasteurization of human serum albumin. Issue 3 (26th December 2016) - Kühnel, Denis; Müller, Sebastian; Pichotta, Alexander; Radomski, Kai Uwe; Volk, Andreas; Schmidt, Torben
Abstract : BACKGROUND: In 2016 the World Health Organization declared the mosquito‐borne Zika virus (ZIKV) a "public health emergency of international concern." ZIKV is a blood‐borne pathogen, which therefore causes concerns regarding the safety of human plasma–derived products due to potential contamination of the blood supply. This study investigated the effectiveness of viral inactivation steps used during the routine manufacturing of various plasma‐derived products to reduce ZIKV infectivity. STUDY DESIGN AND METHODS: Human plasma and intermediates from the production of various plasma‐derived products were spiked with ZIKV and subjected to virus inactivation using the identical techniques (either solvent/detergent [S/D] treatment or pasteurization) and conditions used for the actual production of the respective products. Samples were taken and the viral loads measured before and after inactivation. RESULTS: After S/D treatment of spiked intermediates of the plasma‐derived products Octaplas(LG), Octagam, and Octanate, the viral loads were below the limit of detection in all cases. The mean log reduction factor (LRF) was at least 6.78 log for Octaplas(LG), at least 7.00 log for Octagam, and at least 6.18 log for Octanate after 60, 240, and 480 minutes of S/D treatment, respectively. For 25% human serum albumin (HSA), the mean LRF for ZIKV was at least 7.48 log after pasteurization at 60°C for 120 minutes. CONCLUSION: These results demonstrate that the commonly used virus inactivation processes utilized during the production of human plasma and plasma‐derived products, namely, S/D treatment or pasteurization, are effective for inactivation of ZIKV.